2017
DOI: 10.1080/1547691x.2017.1346009
|View full text |Cite
|
Sign up to set email alerts
|

Transferon™, a peptide mixture with immunomodulatory properties is not immunogenic when administered with various adjuvants

Abstract: Transferon, a human dialyzable leukocyte extract (hDLE), is a biotherapeutic that comprises a complex mixture of low-molecular-weight peptides (< 10 kDa) and is used to treat diseases with an inflammatory component. Some biotherapeutics, including those composed of peptides, can induce anti-drug antibodies (ADA) that block or diminish their therapeutic effect. Nevertheless, few studies have evaluated peptide-derived drug immunogenicity. In this study, the immunogenicity of Transferon was examined in a murine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
2
5
0
1
Order By: Relevance
“…In these assays, we did not observe morphological changes nor alterations of the production of IL-1 β , TNF- α , or IL-6 in macrophage-like THP1 cells (Figure 2). This result agrees with the null immunogenicity previously reported for Transferon® [24]. In contrast, stimulation with LPS (1 μ g/mL) significantly increased the fraction of positive cells, as expected [25]; treatment with LPS was used as positive control in these experiments.…”
Section: Resultssupporting
confidence: 92%
“…In these assays, we did not observe morphological changes nor alterations of the production of IL-1 β , TNF- α , or IL-6 in macrophage-like THP1 cells (Figure 2). This result agrees with the null immunogenicity previously reported for Transferon® [24]. In contrast, stimulation with LPS (1 μ g/mL) significantly increased the fraction of positive cells, as expected [25]; treatment with LPS was used as positive control in these experiments.…”
Section: Resultssupporting
confidence: 92%
“…These results are in agreement with those obtained in our previous study [2], where no antibodies were detected in mice immunized with Transferon® and different adjuvants. But a question arose, the influence of adjuvant over the response obtained with unconjugated peptides of Transferon®, given that in the preliminary study two extra adjuvants were analyzed (Al(OH) 3 and TiterMax® Gold®), we reanalyzed those sera using the bioconjugates as antigens, searching for a signal; nonetheless, this was negligible (Supplemental Figure) in spite of using a more sensible system through the conjugation of Transferon® peptides.…”
Section: Resultssupporting
confidence: 94%
“…In a previous study carried out by our group [2], we demonstrated the null immunogenicity of Transferon® in a murine model even though different immunization routes and adjuvants were employed, highlighting the safeness of the product but delaying the development of a surrogate antibody directed to this hDLE. Therefore, this work was aimed at inducing immunogenicity against this hemoderivative through two strategies; one of them was chemical conjugation of the Transferon® peptides to a carrier protein as the immunogen and the second one was to use the rabbit to achieve the induction of antibodies against peptides in general [21].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations